Religious Heritage Complex and Authenticity: Past and Present Assemblages of One Cypriot Icon - Dorota Zaprzalska (Religions, 2023)
Drawing on data from ethnographic fieldwork, this study focuses on an icon known as Panagia Amirou kept at the Amirou Monastery in Cyprus. Instead of analyzing its unusual form, consisting of two icons from different times inserted one into another, this paper uses the concept of “religious heritage complex” to understand the special status of the icon, the complexity of the assemblages it has joined over time, and the relationships between religion and heritage. The Panagia Amirou icon has become the symbol of the monastery and appears to be crucial for the creation of a shared identity by giving the community the feeling of a connection to the past and continuity of monastic tradition, for as they believe, the icon and the monastery are from the same time. Particular attention is paid to the process of authenticating the icon’s special status. The legend recounts not only the icon’s old age but also its miraculous appearance and the healing power inherent in it from the very beginning, so it authenticates, together with processions, not only the alleged connection of the icon with the beginning of the monastery but also the status of the icon as being miracle-working.